Evaluating Treatment Choice in Patients with Moderate to Severe Psoriasis in the United States: Results from a US Patient Survey - April W. Armstrong; Sayeli Jayade; Sanika Rege; Namita Joshi; Vardhaman Patel; Samaneh Kalirai; Daniel Wolin; Kimberly Boyle; Dipen Patel; Lauren Seigel (Adis, Springer Healthcare, 2024)
Abstract Introduction While multiple treatments are available for moderate to severe psoriasis, patient preferences are rarely systematically studied. This study aims to identify factors associated with choice of a new once-daily oral psoriasis treatment, elicit patient views on treatment characteristics, and rank treatment characteristics by importance. Methods This noninterventional, cross-sectional survey study, conducted from December 2021 to June 2022, recruited US adults with moderate to severe psoriasis. Demographics, clinical characteristics, and perspectives on psoriasis treatment were collected. Factors associated with the choice of a new oral treatment were identified using multivariable logistic regression analysis. Treatment characteristics and reasons for treatment choice were ranked using bivariate comparisons. Results The study included 882 participants [mean (standard deviation; SD) age, 45.7 (12.8) years; female, 67.7%; White, 74.9%]; 92.7% were currently receiving treatment [mean (SD) duration, 2.9 (4.8) years]. Half of participants rated their psoriasis symptoms over the past week as mild, very mild, or nonexistent; 36.5% as moderate; and 12.7% as severe or very severe. Most (66.5%) indicated willingness to start a new oral treatment; 65.0% indicated that the new oral treatment would cause less anxiety than injections/infusions. Participants were significantly more likely to start the new oral treatment if they were currently receiving a tumor necrosis factor inhibitor [odds ratio (OR): 2.1, 95% confidence interval (CI): 1.4-3.1] or ustekinumab (OR: 2.7, 95% CI: 1.6-5.0) versus apremilast (P < 0.001) or if they reported mild (OR: 3.2, 95% CI: 2.0-4.9), moderate (OR: 5.0, 95% CI: 3.1-8.2), or severe (OR: 7.6, 95% CI: 3.9-15.0) psoriasis symptoms compared with those who reported no symptoms in the past week (P < 0.001). Conclusion Most participants indicated willingness to start a new once-daily oral treatment, viewing it as less anxiety provoking than injections/infusions. Current treatment and psoriasis severity affected participants' willingness to start a new oral treatment.